Major perioperative adverse events of peroral endoscopic myotomy: a systematic 5-year analysis - Zhang, Xiao-Cen; Li, Quan-Lin; Xu, Mei-Dong; Chen, Shi-Yao; Zhong, Yun-Shi; Zhang, Yi-Qun; Chen, Wei-Feng; Ma, Li-Li; Qin, Wen-Zheng; Hu, Jian-Wei; Cai, Ming-Yan; Yao, Li-Qing; Zhou, Ping-Hong (Endoscopy, 2016)
Background and study aims: Peroral endoscopic myotomy (POEM) is now a widely used treatment for esophageal achalasia, supported by several large cohort studies. Although major perioperative adverse events (mAE) are rare, in-depth investigations of related risks and preventive measures are lacking. The aim of this study was to systematically assess mAEs during POEM by analyzing their incidence, risks, prevention, and management.Patients and methods: This retrospective single-center analysis included all patients (n = 1680) undergoing POEM between August 2010 and July 2015 at Zhongshan Hospital. Major adverse events were defined as: vital-sign instability, intensive care unit (ICU) stay, hospital readmission, conversion to open surgery, invasive postoperative procedure, blood transfusion, or prolonged (> 5 days) hospitalization for functional impairment.Results: A total of 55 patients (3.3 %, 95 % confidence interval [CI] 2.5 % – 4.2 %) experienced mAEs: delayed mucosal barrier failure (n = 13, 0.8 %; 95 %CI 0.4 % – 1.3 %), delayed bleeding (n = 3, 0.2 %; 95 %CI 0.04 % – 0.5 %), hydrothorax (n = 8, 0.5 %; 95 %CI 0.2 % – 0.9 %), pneumothorax (n = 25, 1.5 %; 95 %CI 1.0 % – 2.2 %), and miscellaneous (n = 6, 0.4 %; 95 %CI 0.1 % – 0.8 %). Four patients (0.2 %) required ICU admission. No surgical conversion occurred, and 30-day mortality was zero. In stepwise multivariate regression, institution experience of < 1 year (odds ratio [OR] 3.85, 95 %CI 1.49 – 9.95), air insufflation (OR 3.41, 95 %CI 1.37 – 8.50), and mucosal edema (OR 2.01, 95 %CI 1.14 – 3.53) were identified as related risk factors. After introducing CO2 insufflation, the mAE rate declined to 1.9 % (95 %CI 1.2 % – 2.7 %) and seemed to plateau after 3.5 years at ~ 1 %.Conclusion: In general, POEM appears to be a safe procedure. Major adverse events were rare and could usually be prevented or anticipated, and were all managed effectively.